Microbiology and Outcome of Peritoneal Dialysis-Related Peritonitis in Elderly Patients: A Retrospective Study in China - Song, Panai; Yang, Dong; Li, Jine; Zhuo, Ning; Fu, Xiao; Zhang, Lei; Zhang, Hongqing; Liu, Hong; Sun, Lin; Liu, Yinghong (Frontiers in Medicine, 2022)
Objective: The number of elderly patients on peritoneal dialysis (PD) has rapidly increased in the past few decades. We sought to explore the microbiology and outcomes of peritonitis in elderly PD patients compared with younger PD patients. Methods: We conducted a retrospective study to analyze the clinical characteristics, causative organism distribution, and outcome of all PD patients who developed peritonitis between September 1, 2014 and December 31, 2020, from Second Xiangya Hospital, Central South University, China. Patients who experienced peritonitis were separated into elderly and younger groups. The elderly was defined as ≥ 65 years at the initiation of PD. Results: Among 1200 patients, 64(33.9%) in elderly (n =189) and 215 (21.3%) in younger (n =1011) developed at least one episode of peritonitis. 394 episodes of peritonitis occurred in 279 patients. 88 episodes occurred in 64 elderly patients, and 306 episodes occurred in 215 younger patients. Gram-positive bacteria were the main causative organisms in elderly and younger patients (43.2% and 38.0%, respectively). Staphylococcus and Escherichia coli were the most common gram-positive and gram-negative bacteria, respectively. Fungal peritonitis in elderly patients was higher compared with younger patients (χ2 = 6.55, P = 0.01). Moreover, Acinetobacter baumannii (χ 2=9.25, P =0.002) and polymicrobial peritonitis (χ 2 = 6.41, P = 0.01) in elderly patients were also significantly higher than that in younger patients. Additionally, elderly PD patients had higher peritonitis-related mortality than younger patients (χ 2 = 12.521, P = 0.000), though there was no significant difference in catheter removal between the two groups. Kaplan-Meier analysis showed that cumulative survival was significantly lower in elderly patients than younger patients (log rank= 7.867, p=0.005), but similar technical survival in both groups (log rank=0.036, p=0.849). Conclusions: This retrospective study demonstrated that elderly PD patients were more likely to develop Acinetobacter baumannii, fungal and polymicrobial peritonitis than younger PD patients. In addition, peritonitis-related mortality was significantly higher in elderly patients, whereas peritonitis-related catheter removal was comparable between elderly and younger PD patients. Understanding microbiology and outcome in elderly patients will help to reduce the incidence of PD-associated peritonitis and improve the quality of life.